Ariel : a novel with Lawrence Block - Block, Lawrence, 1938- (Carroll & Graf Publishers, 1997)
Ariel Jardell, an adopted 12-year-old girl, is possessed, her mother thinks, by jealousy and by forces far more bizarre.An unnerving tale woven together with a fascinating, terrifying child at the center of each twist and turn it takes, this book gives new definition to the old conflict of good versus evil, sane versus insane.